Analysis of Flexural Strength Properties of Jute Fiber Composite for Foot Plate Orthosis Manufacturing - Dian, Elka Ryzki; Agusni Karma; Fitriana, Rina; Widhata, Dhanny (Poltekkes Kemenkes Jakarta I, 2025)
Background: Foot Plate Orthosis (FPO) is an assistive device to prevent foot injuries. Carbon fiber is a commonly used material. Although carbon fiber material provides many advantages, its dependence on imported raw materials is an obstacle. Therefore, alternative materials that are easily available in Indonesia are needed. Jute fiber has the potential to be a strong,elaticity and economical alternative. Objective: To analyze flexural strength properties of jute fiber composites as an alternative material for orthosis foot plates. Methods: The study used a quantitative experimental design that included included creating composite materials with woven of jute fiber, polyester resin using the lamination method. Variations in the number of jute fiber layers were used to determine their effect on flexural strength. Flexural strength testing was conducted using ASTM D790 standard. The test data was analyzed descriptively and statistically to determine the optimal layers that provide the best flexural strength. Results: The test results show that the jute fiber composite with five layers produces the highest flexural strength, which is 50 MPa. The increase in the number of layers is directly proportional to the increase in flexural strength up to the optimum point at five layers. However, jute fiber composites tend to have lower elasticity than synthetic materials such as carbon fiber. Conclusion: Jute fiber composites with the optimal number of layers have flexural strength as orthosis foot plate materials, but their low elasticity limits their effectiveness in dynamic activities.